Evaluation of a Web Portal for Improving Public Access to Evidence-Based Health Information and Health Literacy Skills: A Pragmatic Trial - Austvoll-Dahlgren, Astrid (Public Library of Science, 2012)
BACKGROUND: Using the conceptual framework of shared decision-making and evidence-based practice, a web portal was developed to serve as a generic (non disease-specific) tailored intervention to improve the lay public's health literacy skills. OBJECTIVE: To evaluate the effects of the web portal compared to no intervention in a real-life setting. METHODS: A pragmatic randomised controlled parallel trial using simple randomisation of 96 parents who had children aged <4 years. Parents were allocated to receive either access to the portal or no intervention, and assigned three tasks to perform over a three-week period. These included a searching task, a critical appraisal task, and reporting on perceptions about participation. Data were collected from March through June 2011. RESULTS: Use of the web portal was found to improve attitudes towards searching for health information. This variable was identified as the most important predictor of intention to search in both samples. Participants considered the web portal to have good usability, usefulness, and credibility. The intervention group showed slight increases in the use of evidence-based information, critical appraisal skills, and participation compared to the group receiving no intervention, but these differences were not statistically significant. CONCLUSION: Despite the fact that the study was underpowered, we found that the web portal may have a positive effect on attitudes towards searching for health information. Furthermore, participants considered the web portal to be a relevant tool. It is important to continue experimenting with web-based resources in order to increase user participation in health care decision-making. TRIAL REGISTRATION: ClinicalTrials.gov NCT01266798